The Relationship Between Brands’ Usage and The Body Image of Young Indonesian Women - Alberta Donette Prasanti Nugraha; Nia Sarinastiti (CoverAge: Journal of Strategic Communication, 2023)
Marketing activities by brand on Instagram have an impact on women's body image because the models used by brand tend to represent a standard of beauty that exists in society. However, brand have started using models of all body shapes and sizes to meet the demands of consumers on social media in recent years. This study aims to determine whether there is a relationship between the use of social media Instagram by brand and the body image of young Indonesian women by using the Agenda Setting theory, Body Image through the Multidimensional Body Self Relation Questionnaire-Appearance Scale (MBSRQ-AS). Data for quantitative research were obtained by distributing online questionnaires to young women aged 18-24 years who live in the areas of Jakarta, Bogor, Depok, Tangerang and Bekasi who are active Instagram users through a non-probability sampling technique. Research result states that a relationship between brands’ usage of social media (Instagram) and the body image of young Indonesian women was formed when they were exposed to marketing content featuring models with thin bodies as well as various body shapes and sizes. In addition, they also formed a perception on the content in regard to their needs, interests, and if they found the model ‘interesting’. However, the usage of Instagram by brand did not appear to have a relationship with the behavior of young women as most respondents almost never exercised excessively or limited their diet after seeing the brands’ content.